Model Pembelajaran Berbasis Literasi di Madrasah - Herman Herman (At-Tafkir, 2020)
This article is aimed to describe the implementation of literacy-based learning model in fostering readingand writing interest, developing listening and speaking skill, and mastering information and technology. To these days, teachers seem to fail in constructing literacy-based learning model which lead to the weak culture and tradition of reading, listening and writing among the students, and the low skill in information and technology in this digital era of 4.0. The study was conducted in a qualitative approach employing library research method. Data collection was performed by reading relevant literature associated with the implementation of literacy-based learning model in Madrasah. The result of the study pointed that to implement literacy-based learning model can be performed through the following ways: 1) fostering reading interest, 2) developing writing interest and make it as a habit, 3) training and building up listening skill, 4) training and practising speaking skill, and 5) developing the ability and skill in information technology. The result of the study is recommended to madrasah headmasters and teachers so that they can implement a literacy-based learning model eagerly, accountably, and responsibly. Also, it is expected that they can work together with other stakeholders for the best implementation of the literacy-based learning model.